Google Earth: A New Resource for Shoreline Change Estimation—Case Study from Jaffna Peninsula, Sri Lanka - Warnasuriya, T.W.S.; Gunaalan, K.; Gunasekara, S.S. (My University, 2018)
Estimation of shoreline change using satellite images is considered as a very effective method because the coastline is found highly dynamic. This study focuses to develop a meth odology to detect shoreline changes using satellite imageries obtained from Google Earth platform. The study was carried out in north-east coastline of Jaffna in Sri Lanka. Shorelines from 2002 to 2017 were delineated on the multi-temporal sat ellite images in the Google Earth software by visual interpret ation and change was detected using Digital Shoreline Analysis System in ArcGIS. Tidal variation, digitizing error, and geometric errors were considered to calculate the uncertainty. Mean End Point Rate, mean Shoreline Change Envelop, mean Net Shoreline Movement, and mean Weighted Linear Regression Rate were used as main shoreline change statistics. Result shows that there is net shoreline accretion of 6.13 ± 8.74 m with an annual rate of deposition of 0.5 m/year. During the study period, 76.12% of the observed shoreline is found accreted while the 23.88% of the shoreline is eroded. Mean Uncertainty of the shoreline is 3.73 ± 0.59 m. The study revealed that the satellite images from Google Earth platform can be used for time series analysis of shorelines after appro priate corrections.
Keywords: GIS; google earth; platform; DSAS; remote sensing; shoreline change